2019
DOI: 10.1007/s40195-019-00893-4
|View full text |Cite
|
Sign up to set email alerts
|

Masing Behavior and Microstructural Change of Quenched and Tempered High-Strength Steel Under Low Cycle Fatigue

Abstract: Low cycle fatigue behavior of a quenched and tempered high-strength steel (Q960E) was studied in the strain amplitude ranging from ± 0.5% to ± 1.2% at room temperature. As a result of fatigue loading, the dislocation structural evolution and fracture mechanism were examined and studied by transmission electron microscopy and scanning electron microscopy (SEM). The results showed that this Q960E steel showed cyclic softening at different strain amplitudes, and the softening tendency was more apparent at strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This method can be used to predict W f for any strain amplitude provided the material constants S 1 and S 2 are determined from a sufficient number of LCF tests. The authors 11,12 have validated the applicability of Equation 5 12 with 13 different materials (304L SS, 12 304LN SS, 16 316LN SS, 91 SA333 Gr.6, 16 AA6063, 79 AISI 1018 HR steel, 7 annealed Cu, 119 annealed Al, 119 BLY160 steel, 14 AISI 321 SS, 13 LY225 steel, 25 HSS Q960E, 88 and AL6XN steel 120 ) that include Masing, non-Masing (Type-I) and non-Masing (Type-II) behaviors. 11,12…”
Section: Cpsed Methodsmentioning
confidence: 93%
See 3 more Smart Citations
“…This method can be used to predict W f for any strain amplitude provided the material constants S 1 and S 2 are determined from a sufficient number of LCF tests. The authors 11,12 have validated the applicability of Equation 5 12 with 13 different materials (304L SS, 12 304LN SS, 16 316LN SS, 91 SA333 Gr.6, 16 AA6063, 79 AISI 1018 HR steel, 7 annealed Cu, 119 annealed Al, 119 BLY160 steel, 14 AISI 321 SS, 13 LY225 steel, 25 HSS Q960E, 88 and AL6XN steel 120 ) that include Masing, non-Masing (Type-I) and non-Masing (Type-II) behaviors. 11,12…”
Section: Cpsed Methodsmentioning
confidence: 93%
“…The influence of strain amplitude on the Masing/non‐Masing behavior has been investigated for different classes of materials in the literature 88–90 . In 316LN SS, Roy et al 91 observed Masing behavior at lower strain amplitudes (<±0.5%) and non‐Masing behavior at higher strain amplitudes (>±0.5%).…”
Section: Factors Affecting the Masing/non‐masing Behavior Of Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The plastic strain energy density is an important index for evaluating the fatigue damage of mechanical materials [23]. The calculation method for the plastic strain energy density differs depending on whether the material exhibits mashing behaviour [24,25], which refers to the half-life [26] hysteresis curves of different strain amplitudes, moving the lowest point of each hysteresis curve to a certain point. If the upper half of the hysteresis curve overlaps, the material exhibits mashing behaviour [26].…”
Section: Introductionmentioning
confidence: 99%